Analisis Sentimen Komentar YouTube pada Program Clash of Champions Ruangguru Menggunakan Deep Learning Berbasis LSTM - Iska Rahmawati; Nur Aini (Yayasan Lembaga Studi Makwa, 2025)
The growth of digital platforms such as YouTube has opened massive interactive spaces among users, particularly through comment sections on educational content. This study aims to analyze public sentiment toward Ruangguru's